The role of local governments in flood disaster mitigation in Makassar city - Bahrul Samuindarwan Ishak; Kuntala Chowdhury (Tamalanrea: Journal of Government and Development (JGD), 2024)
This study aims to determine and describe the Role of the Government in mitigating flood disasters in Makassar City as well as factors that influence the government's role in mitigating flood disasters in Makassar City. This type of research uses a qualitative approach with descriptive elaboration. A qualitative approach with descriptive elaboration is a study that aims to obtain an overview to understand and explain the role of local governments in mitigating flood disasters in the city of Makassar. The data collection in this study used observation techniques, interviews, literature studies, and documentation studies. The results showed that the government's role in mitigating flood disasters in the city of Makassar was in the form of improving drainage systems, effective early warning, education and public awareness, and making dams. In addition, the government's efforts to divide flood disaster mitigation into three stages, including pre-disaster, during emergency response, and post-disaster. Factors that influence the role of the government in flood disaster mitigation consist of supporting factors, namely synergy between agencies in the ranks of the Makassar city local government, vertical coordination of BPBD Makassar city with government agencies in higher positions. In addition, the inhibiting factors are, limited resources, changes in land use.